ANALYSIS OF BUDGET MANAGEMENT AND ITS IMPLICATIONS FOR THE ORGANIZATIONAL PERFORMANCE OF THE REGIONAL OFFICE OF THE NATIONAL LAND AGENCY, LAMPUNG PROVINCE - Densa, Ricky; Zakaria, Adam; Pahala, Indra (International Journal of Social Service and Research, 2024)
The National Land Agency of Lampung Province (BPN) Regional Office in the Lampung region faces challenges in managing budget absorption due to a top-down planning process and lack of comprehensive planning documents. However, delays in completing certain works funded by Non-Tax State Revenue (PNBP) reveal ongoing challenges in prioritizing programs and ensuring comprehensive performance evaluation. These challenges require improvements in strategic management and budget synchronization to enhance accountability, effectiveness, and the quality of program and activity results. This research uses a qualitative approach using a case study strategy. The results of this research can provide practical and policy contributions to the Regional Office of the BPN Lampung province in an effort to optimize budget and output produced.